Upscaling of Perovskite Photovoltaics - Jang, Dongju; Yang, Fu; Dong, Lirong; Brabec, Christoph; Egelhaaf, Hans-Joachim (wiley, 2021)
Hybrid organic-inorganic perovskite solar cells have reached a certified efficiency of over 25% during the past decade, which has attracted significant attention as a promising candidate for photovoltaics (PVs) applications. However, the most efficient perovskite solar cells were performed by the spin coating technique, which is extremely limited in commercialization. Besides, the efficiencies of large-area perovskite cells and modules are still significantly lower. There are still some challenges that need to overcome to bridge the efficiency gap between small-area perovskite solar cells and large-area perovskite devices. The most important challenge is how to prepare high-quality perovskite layers using cheaper and scalable techniques with high reproducibility. On the other hand, select and deposit charge extraction/transport layers, and the bottom and top electrodes using cheaper and scalable techniques are also important. In this review, recent progress and challenges of the scalable technologies for solution-based coating and printing methods are summarized and analyzed based on the current progress in scalable technologies for solution-based preparation of large-area perovskite PVs. Based on our analysis, we try to point out the major challenges to overcome to successfully bridge the efficiency gap between small-area perovskite solar cells and large-area perovskite devices. Finally, strategies and opportunities are proposed to promote stable and efficient large-area perovskite PVs toward commercialization.
CRIS-Team Scopus Importer:2024-12-16
Keywords: module; perovskite solar cells; roll-to-roll production; upscaling